The role of finance in inclusive human development in Africa revisited - Simplice Asongu; Rexon T. Nting (African Governance and Development Institute (AGDI), 2021)
This study investigates direct and indirect linkages between financial development and inclusive human development in data panels for African countries. It employs a battery of estimation techniques, notably: Two-Stage Least Squares, Fixed Effects, Generalized Method of Moments and Tobit regressions. The dependent variable is the inequality adjusted human development index. All dimensions of the Financial Development and Structure Database (FDSD) of the World Bank are considered. The main finding is that financial dynamics of depth, activity and size improve inclusive human development, whereas the inability of banks to transform mobilized deposits into credit for financial access negatively affects inclusive human development. Policies should be tailored to improve mechanisms by which credit facilities can be provided to both households and business operators. Surplus liquidity issues resulting from the inability of banks to transform mobilized deposits into credit can be resolved by enhancing the introduction of information sharing offices (like public credit registries and private credit bureaus) that would reduce information asymmetry between lenders and borrowers. This study complements the extant literature by assessing the nexus between financial development and inclusive human development in Africa.
Keywords: E00; G20; I00; O10; 330; Banking; human development; Africa